Kekhasan Moral Kristiani: Ideologis atau Epistemologis? - haryatmoko, Joannes (Jurnal Orientasi Baru, 2009)
Does Christian ethics propose an original moral which is different from other ethics? The golden rule could be the starting point of the search for the uniqueness of the christian ethics. â€Treat others as you would like them to treat you. So treat others as a goal and not as a meansâ€. This golden rule still supposes a reciprocal relationship. So it must be viewed in a new perspective which is of generosity. So the categorical imperative must be completed by â€love your enemies and do good, and lend without any hope of returnâ€ (LukeÂ 6:35). This completion characterizes the logic of generosity which can be claimedÂ is the uniqueness of christian ethics because it transcends the mere logic ofÂ eciprocity of the golden rule. The logic of generosity purifies the christian ethicsÂ rom all kinds of interests and expectations. This radicality of following JesusÂ hrist answers the perplexity of Derrida putting into question of the existence of a sincere gift and pardon. Derridaâ€™s deconstruction confirms mediately theÂ niqueness of christian ethics. Christianism places ethics in a concrete community with all its organizations, traditions, rites, institutions, theologies and the individuals of its members.